The Well-Cemented Total Hip Arthroplasty
DOI: 10.1007/3-540-28924-0_17
|View full text |Cite
|
Sign up to set email alerts
|

What Is Modern Cementing Technique?

Abstract: This chapter gives an overview of cementing technique evolution and defines the current status of modern cementing techniques. Modern cementing techniques aim to improve the mechanical interlock between bone and cement in order to establish a durable interface. The use of distal plug, cement gun, pulsatile lavage and cement pressurising devices have been shown to significantly improve long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…2 For a good long time result, the main focus must be put on the fatigue properties of the cement and the cement-bone interface. 1,3 Therefore, many efforts have been made to improve bone cement by either enhancement of the mechanical properties of PMMA (i.e. fiber reinforcement, vacuum mixing) or improvement at the bone-cement interface through the development of bioactive bone cement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 For a good long time result, the main focus must be put on the fatigue properties of the cement and the cement-bone interface. 1,3 Therefore, many efforts have been made to improve bone cement by either enhancement of the mechanical properties of PMMA (i.e. fiber reinforcement, vacuum mixing) or improvement at the bone-cement interface through the development of bioactive bone cement.…”
Section: Introductionmentioning
confidence: 99%
“…Since PMMA does not adhere to bone, 3,4 a layer of intervening fibrous tissue is formed at the bone-cement interface. 5,6 Therefore, a sufficient penetration of the cement into cancellous bone is needed to provide adequate anchorage of the implant.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have previously reported that polymethyl methacrylate (PMMA) bone cement, widely used for prosthesis fixation, does not bond directly with the bone. Instead, there is always an intervening fibrous tissue, possibly leading to subsequent aseptic loosening [ 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Improvements in cementing technique, which increase the strength and stability of the cement-bone interface by optimization of the cement-bone interlock, have produced improvements in the long-term success of the prosthesis. These include controlling the viscosity of cement at time of insertion [8,[10][11][12], cleaning the bone surface [12][13][14], the use of distal plugs in the femur [13], and pressurization of the cement [15]. In addition to cement interlock, the quality of cancellous bone (its geometry, presence of disease, and mechanical properties) affects the cement-bone interface strength [11].…”
Section: Introductionmentioning
confidence: 99%